The Laboratory Diagnosis of Haemophilus ducreyi - Michelle Alfa (Canadian Journal of Infectious Diseases and Medical Microbiology)
Chancroid is a sexually transmitted infection caused by Haemophilus ducreyi. This fastidious, Gram-negative coccobacilli dies rapidly outside the human host, making diagnostic testing using culture methods difficult. This genital ulcer infection is not common in Canada and, therefore, can often be misdiagnosed. The objective of the present paper is to provide practical approaches for the diagnosis of chancroid in Canadian patients where the prevalence of this infection is low. Issues related to sample collection, sample transport and available diagnostic tests are reviewed, and several alternative approaches are outlined. Although antigen detection, serology and genetic amplification methods have all been reported for H ducreyi, none are commercially available. Culture is still the primary method available to most laboratories. However, the special media necessary for direct bedside inoculation is often not available; therefore, communication with the diagnostic laboratory and rapid specimen transport are essential when chancroid is suspected